Integrasi Pemetaan Agrowisata dan Mitigasi Bencana Tanah Longsor Berbasis Masyarakat di Desa Anggramanis, Karanganyar - Handayani, Kusumaningdyah Nurul; Pranata, David Arya; Muttaqin, Muhammad Luqmanul Vagastya Salman; Syahran, Unggul Aida (PRIMA: Journal of Community Empowering and Services, 2024)
Integration of Agrotourism Mapping and Community Based Landslide Disaster Mitigation in Anggrasmanis Village, Karanganyar. Anggrasmanis Village has the potential to become a tourist village with a variety of destinations, ranging from religious tourism to nature tourism to educational tourism. Its location in Karanganyar Regency, with its fertile soil, adds to the opportunities for regional development in agrotourism management. On the other hand, the steep topography and high rainfall intensity cause some areas to be prone to landslides, despite mitigation efforts that have been made. In fact, the largest landslide disaster in Karanganyar Regency occurred in 2007, claiming 58 lives. Based on this background, community service activities in Anggrasmanis Village, Karanganyar Regency, aim to map areas with tourism potential and identify landslide prone areas to support sustainable development planning. The methods used include field surveys, spatial analysis, and participatory mapping involving the community, village officials, and volunteers from Anggrasmanis Village. The mapping was carried out using editing applications such as CorelDraw, Photoshop, and Adobe Illustrator. The optimization of map use was also carried out using barcode scanning technology, which aims to make it easier for the community to gather information independently through cell phone layers. The results of this activity are thematic maps showing the locations of agrotourism sites and landslide prone zones. The thematic maps are expected to be used by local governments, tourism operators, and the community to make informed decisions and serve as a basis for developing sustainable agrotourism in Anggrasmanis Village.